Mitomycin C and Capecitabine (MiX Trial) for Therapy of Patients with Metastasized, Breast Cancer Pretreated with Anthracycline - Almstedt, Katrin; Fasching, Peter; Scharl, Anton; Rauh, Claudia; Rack, Brigitte; Hein, Alexander; Hack, Carolin; Bayer, Christian M.; Jud, Sebastian; Schrauder, Michael G.; Beckmann, Matthias; Lux, Michael P. (Anticancer Research, 2016)
BACKGROUND/AIM: The aim of this single-arm, prospective, multicenter phase II trial (MiX) was to increase treatment options for women with metastatic breast cancer pretreated with anthracycline and taxane by evaluation of the efficacy and toxicity of the combination of mitomycin C and capecitabine. PATIENTS AND METHODS: From 03/2004 to 06/2007, a total of 39 patients were recruited and received mitomycin C in combination with capecitabine. The primary end-point was to determinate the tumor response according to Response Evaluation Criteria in Solid Tumors and the rate of toxicities (safety). The secondary study objective was the evaluation of the time to progression (i.e. efficacy). RESULTS: The median time to progression was 9.3 months (95% confidence interval=6.6-12.0 months) and the median survival was 12.8 months (95% confidence interval=6.8-18.8 months). Most treatment-related adverse events were mild to moderate. CONCLUSION: Mitomycin C and capecitabine is a good taxane-free option in patients with metastatic breast cancer previously treated with anthracycline.
EVALuna2:33006